2002
DOI: 10.1038/sj.bmt.1703587
|View full text |Cite
|
Sign up to set email alerts
|

How do parents perceive high-dose chemotherapy and autologous stem cell transplantation for their children

Abstract: Summary:Our objective was to understand the parents' perception of children treated in an ASCT unit. Parents (40) of children and adolescents were interviewed by the department psychiatrist-psychoanalyst, over 9 months. They expressed great distress (22), considerable difficulty in assuming their parental role (with feelings of helplessness and guilt), and had distorted relations with the child whose behavior was unusual and incomprehensible (22). The relation with care providers, who should be 'all-powerful' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
2
20
1
2
Order By: Relevance
“…In 2 qualitative studies of parents of children undergoing HSCT, parents expressed their fear of the perils of HSCT and described being either incapable or unwilling to think about the situation or their child’s potential outcome [14,18]. Some actively pushed the possibility that their child might die out of their minds, whereas others simply denied this possibility [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 qualitative studies of parents of children undergoing HSCT, parents expressed their fear of the perils of HSCT and described being either incapable or unwilling to think about the situation or their child’s potential outcome [14,18]. Some actively pushed the possibility that their child might die out of their minds, whereas others simply denied this possibility [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that parents’ contemplation of HSCT risks and adverse outcomes may be influenced by their sense of culpability for a potentially poor outcome, their lack of control over the situation, and the absence of an alternative treatment offering cure [18,25]. The highly cure-oriented setting of HSCT and the social desirability of positive thinking [26,27] also may promote thoughts focused on positive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In 2005 Phipps et al 21 presented data on parents of 151 children undergoing HSCT, studied upon admission and monthly throughout a 6 months period. They reported that there are identifiable predictors of parental distress, such as previous parent and patient illness-related distress, premorbid child internalization behavior problems and parental avoidance of coping, and they suggest that if these predictors can be identified at an early stage one may identify parents who are in need of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…31 Parents find it difficult to assume and fulfill their parental roles in light of the trajectory that childhood cancer treatments inevitably take. 32 Therefore, it is important for doctors as well as the health care nurses-whose major role is the daily care of the child and the parents-to participate in the end-of-life decision-making process. Health care providers need to support parents by letting them think that they can protect their child, while sharing in the experiences through which parents have been able to realize the sense of ''being a parent.''…”
Section: Matsuoka and Naramamentioning
confidence: 99%